MODELS OF EXERCISES IN THE CONTRASTIVE TEACHING OF SERBIAN AND ENGLISH ORTHOGRAPHY - Gavranović, Valentina; Čorboloković, Saša (Metodička teorija i praksa, 2026)
This paper presents models of exercises for the contrastive teaching of Serbian and English orthography. The primary objective is to demonstrate methods for formulating tasks that contrast the orthographic elements of both languages. The paper’s specific objectives are: to apply contrastive analysis and error analysis at the orthographic level; to present models of exercises; to analyze the models from the aspect of teaching and learning effectiveness and cognitive load; and to suggest how to apply these models in teaching and learning orthographic rules of both languages. These models are based on translation, comparison, and the identification of differences, error correction, riddles, and quizzes. Through their application, students become more aware of the differences in orthographic rules and how to apply these rules, with the aim of enhancing and consolidating a more lasting and functional orthographic knowledge of both languages.
Keywords: orthography; spelling rules; contrastive analysis of Serbian and English; error analysis; contrastive tasks